SOCIALIZATION OF THE RELATIONSHIP OF ECONOMIC GROWTH TOWARDS INTEREST IN DIGITAL INVESTMENT TO STUDENTS OF THE FACULTY OF SOCIAL SCIENCES AND FACULTY OF ECONOMICS UNIVERSITAS MALIKUSSALEH - Reza Juanda; Rico Nur Ilham; Fuadi; Arliansyah; Muttaqien; Sufi (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
Socializing the Relationship between Economic Growth and Interest in Digital Investment to Students of the Faculty of Social Sciences and Faculty of Economics, Malikussaleh University is very important in this digital era. Rapid economic growth in the digital era has created various new investment opportunities, including in digital sectors such as cryptocurrencies, technology stocks and other online investment platforms. However, students' understanding and interest in digital investment still varies. Discussion of digital-based financial literacy in investment has shown its impact in increasing students' awareness and interest in making digital investments and digital-based financial literacy can help students understand the use of digital investment applications and the risks of loss and profit opportunities that can be obtained. In the digital era, mastery of technology is an important key in winning business competition, as well as in understanding financial investment opportunities by utilizing financial technology. The Bachelor of Business Management and Administration program is designed to prepare graduates who are able to create innovations in the financial sector to meet investment needs. Economic growth plays an important role in increasing interest in digital investment among students. Therefore, it is recommended that educational institutions strengthen financial and economic education to prepare students to face the digital investment era. Apart from that, more intensive outreach regarding digital investment opportunities and risks is needed to increase investment literacy among students.